Anti-inflammatory activity of a water-soluble polysaccharide from the roots of purple sweet potato. Issue 65 (29th October 2020) - Sun, Jian; Gou, Yarun; Liu, Jun; Chen, Hong; Kan, Juan; Qian, Chunlu; Zhang, Nianfeng; Niu, Fuxiang; Jin, Changhai
Abstract : A water-soluble polysaccharide from purple sweet potato roots played anti-inflammatory roles by regulating inflammatory cytokines, gut microbiota and antioxidant defense system. Abstract : In this study, a water-soluble polysaccharide was isolated from purple sweet potato roots. The in vitro and in vivo anti-inflammatory effects of the polysaccharide were evaluated by lipopolysaccharide (LPS)-induced inflammatory RAW264.7 macrophages and mice, respectively. The in vitro anti-inflammatory assay showed that the polysaccharide could effectively inhibit the overproduction of nitric oxide and pro-inflammatory cytokines (TNF-α, IL-1β, IL-6) while increasing the secretion of anti-inflammatory cytokine (IL-10). The in vivo anti-inflammatory assay revealed that mice administered with the polysaccharide showed higher IL-10, SOD, and T-AOC levels but lower TNF-α, IL-1β, IL-6 and MDA levels as compared to the LPS-treated model. Meanwhile, mice administered with the polysaccharide showed increased abundance of Lachnospiraceae, Lactobacillales and Parabacteroides but decreased amounts of Psychrobacter and Staphylococcus as compared to the LPS model group. Moreover, mice administered with polysaccharide showed enhanced production of short chain fatty acids by gut microbiota in the lipopolysaccharide-induced inflammatory mice. Our results suggested that the water-soluble polysaccharide from purple sweet potato roots could be utilized as a novel anti-inflammatory agent.